The Impact Of Object Description Ac Tivities In Improfing Students Speaking Skills At MTs Sirajul Huda - Maemunah; Herman; Hasbullah; Danul Aristiawan (PENA : Jurnal Pendidikan Bahasa, Sastra, & Pengajaran, 2025)
Object Description Activities Technique to Improve Students’ Speaking Skills at MTs Sirajul Huda. Thesis. English Education Department. Undergraduate Program. University of Qamarul Huda Badaruddin Bagu. 2025. This research was motivated by phenomena in the process of teaching and learning English, where students have low speaking ability several contributing factors were students have lack of confidence to speak in front of the class and also students’ vocabulary was still very low. So the students need a technique that can help them to improve their speaking skills, one of which is the Object Description Activities technique. The purpose of this research was to find out whether or not Object Description Activities technique can improve students’ speaking skills at MTs Sirajul Huda. This study used pre-experimental design. The sample was 20 eighth grade students of MTs Sirajul Huda. The instrument in this study used a speaking test in the form of Lombok tourism which familiar to students to collect data. First, the researcher gave a pretest, second gave treatment, and third the researcher gave a posttest. Researcher analyzed the data using the SPSS computer program to compare data results, the tests used were descriptive statistics, normality tests and T-tests. Based on the results of this study, it can be concluded that: (1) the use of Object Description Activities technique was very effective to improve students’ speaking ability. This can be seen from the results of the study which show the average value before treatment was 56.20 and the average value after treatment was 67.90. (2) the use of storytelling techniques was very suitable for use in the learning process, as evidenced by the students’ expressiveness and enthusiasm which makes the class more fun